2013
DOI: 10.1007/s12253-013-9643-z
|View full text |Cite
|
Sign up to set email alerts
|

There is no Significant Association Between Death Receptor 4 (DR4) Gene Polymorphisms and Lung Cancer in Turkish Population

Abstract: Death receptor 4 (DR4) gene is a candidate tumor suppressor gene that has a role in apoptotic pathway. It was reported in literature that polymorphisms in DR4 gene lead to susceptibility to many cancers. In accordance with this information, we aimed to investigate the association between G422A, C626G, A683C and A1322G polymorphisms in DR4 gene and lung cancer. We selected 60 patients with lung cancer (LC) and 30 healthy, sex and age matched volunteers randomly. Four polymorhisms, G422A, C626G, A683C and A1322G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…, Chen B (Frank et al, 2009 indicated that the C626G polymorphism in DR4 gene is associated with cancer susceptibility by a meta-analysis. However, three studies have been published since 2009 increasing the number of cancer (Chen et al, 2009;Korner et al, 2012;Tastemir-Korkmaz et al, 2013). In our meta-analysis indicates DR4 C626G polymorphism is associated with cancer in Caucasian susceptibility.…”
Section: 2889 Association Of Dr4 (Trail-r1) Polymorphisms With Cancementioning
confidence: 56%
See 1 more Smart Citation
“…, Chen B (Frank et al, 2009 indicated that the C626G polymorphism in DR4 gene is associated with cancer susceptibility by a meta-analysis. However, three studies have been published since 2009 increasing the number of cancer (Chen et al, 2009;Korner et al, 2012;Tastemir-Korkmaz et al, 2013). In our meta-analysis indicates DR4 C626G polymorphism is associated with cancer in Caucasian susceptibility.…”
Section: 2889 Association Of Dr4 (Trail-r1) Polymorphisms With Cancementioning
confidence: 56%
“…And genetic susceptibility to cancer has been a research focus on scientific community. Recently, DR4 gene variants in the etiology of cancers Korkmaz D (Tastemir-Korkmaz et al, 2013) find A683C polymorphism the CC variant may be the protective variant in Turkish population with lung cancer. The same result also in an evidence-based meta-analysis by Chen B (Chen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…There were fourteen studies investigating the association of DR4rs20575 with cancer risk [10], [19], [21], [22], [25], [28], [40]–[46] but we have excluded two studies of Kazuya Kuraoka 2005 [43] and Verònica Fernàndez 2004 [44] because these studies either deviated from HWE (p<0.05) [43] or used tissue samples [44] for polymorphism analysis. We combined the results of our study with the rest 12 eligible studies [10], [19], [21], [22], [25], [28], [40][42], [45], [46] to calculate pooled OR for 4731 cases/5029 control and found no significant overall association with risk of cancer [C vs. G: OR = 1.05 (0.97–1.12), p = 0.222; CC vs. GG: OR = 1.07 (0.94–1.22), p = 0.291; CG vs. GG: OR = 1.08 (0.92–1.27), 0.352; CC+CG vs. GG: OR = 1.09 (0.94–1.26), p = 0.268; Table 6 and Figure S1 in File S1].…”
Section: Resultsmentioning
confidence: 99%
“…We combined the results of our study with the rest 12 eligible studies [10], [19], [21], [22], [25], [28], [40][42], [45], [46] to calculate pooled OR for 4731 cases/5029 control and found no significant overall association with risk of cancer [C vs. G: OR = 1.05 (0.97–1.12), p = 0.222; CC vs. GG: OR = 1.07 (0.94–1.22), p = 0.291; CG vs. GG: OR = 1.08 (0.92–1.27), 0.352; CC+CG vs. GG: OR = 1.09 (0.94–1.26), p = 0.268; Table 6 and Figure S1 in File S1]. On subgroup analysis, no significant association was found amongst any groups after ethnicity or cancer site based subgroupings.…”
Section: Resultsmentioning
confidence: 99%
“…Since the frequency of variant genotype of this polymorphisms of DR4 228 was low in our population, we could not observe any significant independent associations. Frank et al and Taştemir et al were also reported non-significant association with colorectal and lung cancer risk [10,19]. The haplotype analysis of DR4 (141, 209, and 228) and five haplotypes (G-C-C, G-G-C, A-C-A, A-G-A, and A-G-C) demonstrated higher risk, although statistically significant results persist only with two haplotypes (A-G-A and A-G-C) after applying Bonferroni correction for multiple comparisons with PCa.…”
Section: Discussionmentioning
confidence: 98%